Brooke-Spiegler syndrome: report of 10 patients from 8 families with novel germline mutations: evidence of diverse somatic mutations in the same patient regardless of tumor type - Sima, Radek; Vanecek, Tomas; Kacerovska, Denisa; Trubac, Pavel; Cribier, Bernard; Rutten, Arno; Vazmitel, Marina; Spagnolo, Dominic V; Litvik, Radek; Vantuchova, Yvetta; Weyers, Wolfgang; Pearce, Robert L; et al. (Diagnostic molecular pathology, 2010)
Brooke-Spiegler syndrome (BSS) is an inherited autosomal dominant disease characterized by the development of multiple adnexal cutaneous neoplasms including spiradenoma, cylindroma, spiradenocylindroma, and trichoepithelioma (cribriform trichoblastoma). BSS patients have various mutations in the CYLD gene, a tumor suppressor gene located on chromosome 16q. Our search of the literature revealed 51 germline CYLD mutations reported to date. Somatic CYLD mutations have rarely been investigated. We studied 10 patients from 8 families with BSS. Analysis of germline mutations of the CYLD gene was performed using either peripheral blood or nontumorous tissue. In addition, 19 formalin-fixed paraffin-embedded tumor samples were analyzed for somatic mutations, including loss of heterozygosity studies. A total of 38 tumors were available for histopathologic review. We have identified 8 novel germline mutations, all of which consisted of substitutions, deletions, and insertions/duplications and all except one led to premature stop codons. The substitution mutation in a single case was also predicted to disrupt protein function and seems causally implicated in tumor formation. We demonstrate for the first time that somatic events, loss of heterozygosity, or sequence mutations may differ among multiple neoplasms even of the same histologic type, occurring in the same patient.
Keywords: senioři; deubikvitinizační enzym CYLD; cytologické techniky; Deubiquitinating Enzyme CYLD; zdraví rodiny; Heterozygote; molekulární patologie; Skin Neoplasms; missense mutace; Middle Aged; INDEL Mutation; mužské pohlaví; Codon, Nonsense; nesmyslný kodon; Adult; mladý dospělý; Mutation, Missense; mutace INDEL; Family Health; Young Adult; nádorové supresorové proteiny; Humans; nádory kůže; Cytological Techniques; Tumor Suppressor Proteins; lidé středního věku; Chromosome Disorders; dospělí; zárodečné mutace; Aged; Germ-Line Mutation; Pathology, Molecular; chromozomální poruchy; lidé; Male; heterozygot